Atom probe informed simulations of dislocation–precipitate interactions reveal the importance of local interface curvature. (15th June 2015) - Prakash, A.; Guénolé, J.; Wang, J.; Müller, J.; Spiecker, E.; Mills, M.J.; Povstugar, I.; Choi, P.; Raabe, D.; Bitzek, E.
Graphical abstract: Abstract: The interaction of dislocations with precipitates is an essential strengthening mechanism in metals, as exemplified by the superior high-temperature strength of Ni-base superalloys. Here we use atomistic simulation samples generated from atom probe tomography data of a single crystal superalloy to study the interactions of matrix dislocations with a γ ′ precipitate in molecular dynamics simulations. It is shown that the precipitate morphology, in particular its local curvature, and the local chemical composition significantly alter both, the misfit dislocation network which forms at the precipitate interface, and the core structure of the misfit dislocations. Simulated tensile tests reveal the atomic scale details of many experimentally observed dislocation–precipitate interaction mechanisms, which cannot be reproduced by idealized simulation setups with planar interfaces. We thus demonstrate the need to include interface curvature in the study of semicoherent precipitates and introduce as an enabling method atom probe tomography-informed atomistic simulations.